"Consent is sexy": A poster campaign using sex-positive images and messages to increase dyadic sexual communication. Issue 8 (17th November 2019) - Hovick, Shelly R.; Silver, Nathan
Abstract: Objective : "Consent is Sexy" (CIS) is a poster campaign incorporating sex-positive messages to promote consent and increase sexual communication among college students. We assess reactions to the campaign and associations between campaign recall and communication attitudes and behaviors. Participants: Male and female undergraduates at a Midwestern university were recruited ( N  = 284). Methods: A cross-sectional survey was conducted. t -Tests, logistic and multiple linear regressions were used to analyze the data. Results: Over half (56%) of participants recalled the campaign and reactions were positive. Students who recalled CIS had more positive attitudes towards sexual communication ( p  = .04) and greater perceived behavioral control (PBC; p  < .01). Conclusions: Results show many students paid attention and reacted positively to CIS posters and results offer dissemination insights. Consent campaigns should continue to cultivate positive attitudes and PBC in regards to sexual communication.